Analysis and Assessment of Seismic Hazard for the Azov-Black Sea Recreation Area - ZARETSKAYA, Marina (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.v11.7(47).08, 2020)
One of the geological structures accountable for the implementation of seismic potential of the region is the largest vertical faults in the Earth’s interior, where earthquake foci are usually located. This article is aimed at developing a better method for calculation of stresses and strains that occur in such seismogenic areas. According to the results of the analysis of data collected during the expeditionary work, the geophysical medium is modeled by a block structure in the form of a half-space with a cut rectangular parallelepiped, which is divided into five block elements. The state of material in the geological medium is described in each block by motion equations for a homogeneous, isotropic elastic medium in the Lamé form. Following the block element method, the algorithm of the differential factorization method is implemented in each block. Based on the numerical analysis results, the main trends in contact stresses and dynamics of displacement amplitudes were determined depending on the mechanical property values of the block material and the geometric parameters of the structure.